Plays one - Hare, David, 1947- (London ; Boston : Faber and Faber, 1996)
A collection of David Hare plays from the 1970s.
Slag -- Teeth 'n' smiles -- Knuckle -- Licking Hitler -- Plenty.
ENH
Karim International
Keywords: English drama